GEOLOGY, SEDIMENTOLOGICAL AND HYDRAULIC CONDUCTIVITY OF AJALI POTENTIAL RESERVOIR SANDSTONE EXPOSED AROUND GRA IN IDAH, NORTHERN ANAMBRA BASIN - Yusuf, I.; Obaje, N. G.; Adedosu, T. A.; Adeoye, J. A.; Adamu, L. M.; Tsado, F.; Gana, E. Y. (FUDMA JOURNAL OF SCIENCES, 2023)
The Ajali sandstone is a possible reservoir rock in the Lower Benue Trough (LBT)/Anambra Basin (AB), and understanding its geological, sedimentological distribution is essential for accurate prediction of fluid flow dynamic. Geological, granulometric analysis and laboratory hydraulic conductivity test are integrated for this investigation. Results from geological studies reveals three sandstone lithofacies; namely; AJALI L2A a sandstone intermixed with siltstone, lamination, bioturbated, and crossed bedded, AJALI L2B sandstone mixed  with silty clay, crossed bedded and bioturbated and AJALI L2C an excessive weathered sandstone with visible ripple and ridges with all sedimentary features supporting the earlier proposed fluvio-deltaic depositional environments. The granulometric analysis reveals medium to coarse grain, poorly sorted sandstone lithofacies. Hydraulic conductivity test for AJALI L2A crossed bedded and lamination sandstone contributes smaller pore spaces between grains, which reduce overall interconnectivity of the pore network primarily decreasing the fluid hydraulic flow conductivity and thus lowers the permeability value to 75mD. While in the AJALI L2B intermixed with siltstone and clay sandstone, lowers porosity; but cross-bedding may have contributed positively to increase in permeability value to 1850 mD in this lithofacies. The weathered AJALI L2C sandstone with visible ripples and ridges significantly affect the physical properties and pore spaces obliteration by iron oxide, by contributing to reduction in the permeability value to 60 mD. In overall it is concluded that the Ajali sandstones generally will exhibits an average moderate permeability of 662 mD.
Keywords: Ajali sandstone; sedimentological distribution; granulometric analysis